2022
DOI: 10.3389/fbioe.2022.939441
|View full text |Cite
|
Sign up to set email alerts
|

Research progress in membrane fusion-based hybrid exosomes for drug delivery systems

Abstract: Liposomes are the earliest and most widely used nanoparticles for targeted drug delivery. Exosomes are nanosized membrane-bound particles and important mediators of intercellular communication. Combining liposomes and exosomes using various membrane fusion methods gives rise to a novel potential drug delivery system called membrane fusion-based hybrid exosomes (MFHE). These novel MFHEs not only exhibit potential advantageous features, such as high drug loading rate and targeted cellular uptake via surface modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 83 publications
0
21
0
Order By: Relevance
“…The western blotting and Coomassie brilliant blue staining results con rmed a similar protein expression on HE and exosome. However, it is reported that the shear stress generated during the extrusion process may damage the protein integrity of exosomes [37]. Here, the intensity of the protein bands of HE and exosome in both western blotting assay and Coomassie brilliant blue staining was comparable, indicating that the membrane extrusion frequency (15 times) has little impact on protein degradation.…”
Section: Discussionmentioning
confidence: 66%
“…The western blotting and Coomassie brilliant blue staining results con rmed a similar protein expression on HE and exosome. However, it is reported that the shear stress generated during the extrusion process may damage the protein integrity of exosomes [37]. Here, the intensity of the protein bands of HE and exosome in both western blotting assay and Coomassie brilliant blue staining was comparable, indicating that the membrane extrusion frequency (15 times) has little impact on protein degradation.…”
Section: Discussionmentioning
confidence: 66%
“…The natural incubation process for membrane fusion involves the spontaneous fusion of lipid membranes through electrostatic or hydrophobic interactions based on the physicochemical components of mixed vesicles. This process has a low risk of damaging the vesicles and their contents but has a low fusion efficiency [ 49 ]. Lin et al used this process to create an exosome–liposome hybrid for gene therapy, encapsulating the CRISPR/Cas9 expression vector [ 71 ].…”
Section: Strategies Of Membrane Fusionmentioning
confidence: 99%
“…The fusion of EVs with liposomes, exosomes, and cell membranes offers an increased loading capacity, stability, and biocompatibility, with reduced immunogenicity [ 45 , 46 , 47 ]. While there were previous reviews that briefly mentioned the potential of liposome and exosome fusion as a novel approach for therapeutic applications [ 48 , 49 , 50 ], no previous review has focused on the EVs fusion strategy and its biomedical applications in diagnostics and therapeutics. This study focuses on bioengineering EVs through membrane fusion strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides larger size, hybrid exosomes often possess slightly reduced ZP compared to liposomes due to the initial negative charges of the exosomes ( Bhattacharjee, 2016 ). The following exosomal imaging will reveal confirmation of the fusion ( Bhattacharjee, 2016 ; Liu et al, 2022 ). Flow cytometry and western blot analysis will further confirm the anti-ErbB4 ligand’s existence on the surface of liposome-exosome hybrid extracts ( Lin et al, 2018 ; Alghuthaymi et al, 2021 ).…”
Section: Evaluation Of Strategymentioning
confidence: 99%